Differential regulation of gene co-expression modules in muscles and liver of preterm newborns - Janovska, Petra; Kobets, Tatyana; Steiner Mrazova, Lenka; Svobodova, Michaela; Tesarova, Marketa; Kopecky, Pavel; Zouhar, Petr; Rossmeisl, Martin; Stranecky, Viktor; Kmoch, Stanislav; Kopecky, Jan (Frontiers in Cell and Developmental Biology, 2025)
BackgroundNewborns undergo rapid metabolic and organ adaptations after birth, which are compromised in premature newborns, leading to adverse health outcomes. Molecular mechanisms underlying these transitions remain poorly understood due to limited tissue availability. To address this gap, we characterized tissue transcriptomes using autopsy samples from a unique newborn cohort.MethodsWe analyzed liver (LI), heart (HM), and skeletal muscle (SM) transcriptomes using RNA sequencing in 41 predominantly premature newborns who died shortly after birth. Nearly 14,000 protein-coding gene transcripts per tissue were detected.ResultsTissues exhibited distinct expression profiles, with LI showed the highest number of tissue-specific genes. SM gene expression correlated strongly with gestational age at birth (i.e., the prenatal development), while LI was influenced by the duration of postnatal survival (i.e., the postnatal development). HM displayed minimal changes, suggesting stable myocardial metabolism during the perinatal transition. Weighted Gene Co-expression Network Analysis (WGCNA) identified tissue-specific gene co-expression modules linked to clinical traits such as gestational age, birth weight, survival duration, nutrition, and exposure to catecholamine treatment. The key functional annotations, validated by differential expression analysis, revealed that LI and SM modules were enriched for mitochondrial metabolism and oxidative phosphorylation genes, with more pronounced prenatal development in SM, and a postnatal increase in both tissues. Data suggests that energy metabolism in SM matures first, followed by the development of muscle functions. Hepatic modules were associated with a postnatal increase in the steroid hormone/xenobiotic metabolism, and a decline in hematopoietic activity. Robust annotations to ribosome activity suggested tissue-specific changes in protein synthesis, which declined prenatally in SM, postnatally in HM. Notably, the supply of exogenous glucose and nutrition type were strongly associated with hepatic gene expression, highlighting the central role of the liver in postnatal metabolic adaptation.ConclusionOverall, our study highlights tissue-specific perinatal gene regulation, with mitochondrial maturation emerging as a crucial driver of postnatal adaptation, explaining vulnerabilities in preterm infants. We provide a unique resource for characterizing developmental changes in tissue transcriptomes during the fetal-to-neonatal transition in human newborns.